Surface characteristics of nanoclay modified with different alkylamonium ions - Olalekan, Salawudeen Taofeeq; Muyibi, Suleyman Aremu; Yusof, Faridah; Al-Khatib, Ma'an Fahmi Rashid; Shah, Qasim Hussain; Qudseih, Isam Y. (2009)
The molecular chain length of alkylamonium has a pronounced effect on clay surface polarity, and hence affects the interaction between the polymer matrix and organoclay reinforcement. In order to achieve intercalative or exfoliative dispersion in polymer nanocomposite preparation, surface treatments are always employed using ion exchange process. Several species of alkylamonium ions with different carbon chain length have been used in clay modification without any basis for comparison. The present work investigates the behavioral characteristic of clay surfaces when treated with different alkylaminium ions. Three different organophilic clay samples were prepared using Dodecylamine, Octadecylamine and Cetyltrimethyl ammonium bromide with C12, C18 and C19 carbon chain respectively. The organophilic clays produced were analyzed for surface activeness using Field Emission Scanning Electron Microscopy (FESEM) and Fourier Transform Infrared Spectroscopy (FTIR) and compared with pure, unmodified nanoclay. FESEM/EDX analysis shows certain degree of modification with 7.27% composition of carbon in OCT treated clay. FTIR spectra show that the organophilic clays have varying degree of functional group attachment irrespective of modifier’s carbon chain length. These results have shown that longer chain length does not necessary translate to a more hydrophilic clay or better surface activeness.